PEDAGOGICAL FOUNDATIONS OF DEVELOPING INTELLECTUAL LITERACY IN SCHOOLCHILDREN - Matmuratova, Gulistan Kamalatdinovna (SCIENCE and SOCIETY, 2026)
This article examines the essence and structure of intellectual literacy, its role in developing critical and logical thinking, as well as the significance of modern pedagogical technologies in forming independent thinking, creative abilities, and problem-solving skills in schoolchildren.
Keywords: intellectual literacy; critical thinking; logical thinking; pedagogical technologies; independent learning; creativity; competence; quality of education